A review of security attacks and intrusion detection in the vehicular networks - Tarak Nandy; Rafidah Md Noor; Raenu Kolandaisamy; Mohd Yamani Idna Idris; Sananda Bhattacharyya (Journal of King Saud University: Computer and Information Sciences, 2024)
With the proliferation of Vehicular Ad Hoc Networks (VANETs), ensuring the security and integrity of communication within these networks has become a paramount concern. This paper elaborates on the architecture, characteristics, security services, and various threats in the VANET. Moreover, this paper presents a comprehensive review of Intrusion Detection Systems (IDS) designed for VANETs, aiming to thoroughly understand the challenges, existing solutions, and future directions in this dynamic field. A discussion of the current practices on the evaluation techniques, tools, and datasets is shown. The paper emphasises the need for adaptive and resource-efficient IDS mechanisms, real-world validation, and a deeper exploration of the practical impact of security threats on specific vehicular functionalities. This review serves as a foundation for future research directions to enhance the security of VANETs, contributing to the evolution of intelligent transportation systems.